Anonymization: Securing privacy in IoT. Issue 6 (17th August 2020) - Kaur, Jashanpreet; Sengupta, Jyotsna
Abstract: The convergence of object automation with the association of internet system has become very communal in our routine life. At home, health centres, industries etc. each field has internet-related control systems installed to support organization's proper execution, thereby, increasing the efficiency and saving time. Beside multi-fold benefits, IoT has brought a plethora of privacy risks and security issues. To maintain the privacy of both, the user and the objects many counter measures are carried out and techniques have been found to address illegitimate access and minimize their effect on private data, communication, location etc. The paper focuses on the IoT threats related to individual's identity and the various techniques like anonymization to preserve and protect individual's identity.